Architectural fragments consisting of Hero Stones (Memorial Stones) - Temples of India Project Team (Jio Institute, 2024)
A dozen architectural fragments, mainly consisting of hero stones (memorial stones), along with some pillar and sculptural fragments. The hero stones were installed here after being found scattered in the temple premises and the vicinity of the village. Today these are propitiated as ‘veeron ke pathar’, depicting the journey of the hero (veer), through different panels, in whose memory the steles were installed.